The healthy donor effect and survey participation, becoming a donor and donor career. Issue 1 (8th December 2022) - Brodersen, Thorsten; Rostgaard, Klaus; Lau, Cathrine Juel; Juel, Knud; Erikstrup, Christian; Nielsen, Kasper Rene; Ostrowski, Sisse Rye; Titlestad, Kjell; Sækmose, Susanne G.; Pedersen, Ole B. V.; Hjalgrim, Henrik
Abstract: Background: The healthy donor effect (HDE) is a selection bias caused by the health criteria blood donors must meet. It obscures investigations of beneficial/adverse health effects of blood donation and complicates the generalizability of findings from blood donor cohorts. To further characterize the HDE we investigated how self‐reported health and lifestyle are associated with becoming a blood donor, lapsing, and donation intensity. Furthermore, we examined differences in mortality based on donor status. Study Design and Methods: The Danish National Health Survey was linked to the Scandinavian Donations and Transfusions (SCANDAT) database and Danish register data. Logistic‐ and normal regression was used to compare baseline characteristics and participation. Poisson regression was used to investigate future donation choices. Donation intensity was explored by the Anderson‐Gill model and Poisson regression. Mortality was investigated using Poisson regression. Results: Blood donors were more likely to participate in the surveys, OR = 2.45 95% confidence interval (2.40–2.49) than non‐donors. Among survey participants, better self‐reported health and healthier lifestyle were associated with being or becoming a blood donor, donor retention, and to some extent donation intensity, for example, current smoking conveyed lower likelihood of becoming a donor, OR = 0.70 (0.66–0.75). We observed lower mortality for donors and survey participants, respectively, compared with non‐participating non‐donors. Conclusion: We provide evidence that blood donation is associated with increased likelihood to participate in health surveys, possibly a manifestation of the HDE. Furthermore, becoming a blood donor, donor retention, and donation intensity was associated with better self‐reported health and healthier lifestyles.